MATERIAL PROCESSING TECHNOLOGIES - Adina TĂTAR; Nicoleta MIHUŢ; Georgi VELEV (Journal of Research and Innovation for Sustainable Society)
The development of electrophysical processing methods and their use in production marked a major advance in the technology of processing materials, inasmuch as electricity became a working agent instead of an auxiliary means of mechanical processing. Environmental protection ranks high in public opinion, and has become an important part of market economy. Especially industrial production is linked with risks to the environment. Despite various advantages, these processes may generate solid, liquid or gaseous by-products presenting hazards for workers or the environment. The sort and quantity of the hazardous substances, and suitable measuring methods are discussed. Furthermore, strategies to reduce emissions and to protect environment from possible impacts are explained. The increasing use of such methods in industry is due to their high productivity and to the feasibility of performing production operations that are not possible with mechanical methods. The work presents the results of mathematical modeling of polymer-modified carbon materials microwave heating, checked the adequacy of the model and practical recommendations for the industrial manufacture of products by SPE using short microwave heating for mechanical engineering.